FAKTOR DETERMINAN PERGERAKAN HARGA SAHAM ISLAMIC INDEKS PERIODE 2008 – 2018 - Dika Zanuar Virgantara; Eka Handriani (Faculty of Economics and Business | Universitas Diponegoro, 2020)
This study aims to determine the effect of EPS, NPM, DER, CR and PER on stock prices on the Jakarta Islamic Index (JII) for the period 2008-2018 listed on the Indonesia Stock Exchange. This type of research is causal associative research. The research population is 30 companies. The sampling technique is a purposive sampling technique and obtained a sample of 16 companies. Data analysis methods used are correlation, regression, determination, t test and F test. The results of the study show that partially EPS and NPM variables partially have a significant effect on stock prices, while DER, CR and PER variables partially have no significant effect and have a direction negative towards share prices on the Jakarta Islamic Index (JII) for the period 2008-2018 listed on the Indonesia Stock Exchange.